Spectrum of upper gastrointestinal bleed in patients with cirrhosis of liver - Bhattarai, Subash; Dewan, Khus Raj; Shrestha, Gaurav; Patowary, Bhanumati Saikia (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Acute upper gastrointestinal (UGI) bleeding is a serious medical problem in patients with cirrhosis of liver associated with high mortality. Gastro-oesophageal variceal bleed is the most common complication of portal hypertension in patient with liver cirrhosis. This study was undertaken to establish the causes of UGI bleed in cirrhosis, their relative incidences, clinical presentation , endoscopic findings, outcomes during hospitalization including rebleeding and mortality were studied. Materials & Methods: One hundred and twenty patients with clinical features, sonological and endoscopic evidence of portal hypertension and cirrhosis of liver who presented with upper gastrointestinal bleed were included in the study. After haemodynamic stability, each patient underwent UGI endoscopy usually within 12 hours and the aetiology with diagnostic findings were documented. Results: Ruptured oesophageal varices was the most common cause of UGI bleed in cirrhotic patients. Non variceal causes of UGI bleed accounted for 33.3 % of cases. The majority of non variceal bleed was peptic ulcer disease and accounted for 19.2 % of total UGI bleed in liver cirrhosis. This was followed by portal hypertension gastropathy, erosive gastropathy, mallory-weiss tear and others. Conclusion: The most frequent causes of acute gastrointestinal bleeding in cirrhosis was oesophageal varices. Peptic ulcer disesase is also a common aetiology of UGI bleed in cirrhosis. Cirrhotic patients with variceal etiology have more chances of rebleeding and have higher mortality than those with non variceal aetiologies.